Retirement Arrangements and the Laity at Religious Houses in Pre-Reformation Devon - Fizzard, Allison (Florilegium, 2005)
This article studies the retirement arrangements known as corrodies, which could be purchased by lay people for their retirement at religious houses; superiors of religious houses could also choose to grant corrodies to monastic servants and, in some cases, were obliged to provide them to royal nominees. Corrodies could consist of a combination of entitlements such as cash allowances, housing, and allotments of firewood, candles, bread, ale, and cooked food. This article examines corrodies held by married couples, chaplains, teachers, Crown servants, and single men in the English county of Devon in the years before the dissolution of the monasteries, and suggests that such arrangements may have been more prevalent in this period than has hitherto been thought.